EKSTRAKSI MINYAK ATSIRI DARI RIMPANG TEMU IRENG (Curcuma aeruginosa Roxb) DENGAN PELARUT ETANOL DAN N-HEKSANA - Arsa, Abdullah Kunta; Achmad, Zubaidi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
Indonesia has various natural resources for traditional medication which have been used hereditary. One of them is Curcuma aeruginosa Roxb. It contains essential oil which has not been optimally utilized. Based on some researches, there are some types of essential oil which have been proved to gain both physical and emotional condition of somebody. The research of temu ireng essential oil is conducted by extracting the oil using volume and solvent variances. The solvents variance and its volume are ethanol (250 ml, 300 ml, 350 ml, 400 ml, dan 450 ml) dan n-hexane (250 ml, 300 ml, 350 ml, 400 ml, dan 450 ml). Subsequently, the extract oil is purified by using distillation apparatus in order to generated Curcuma aeruginosa Roxb essential oil. The analysis of absorbance in each cycle of volume variant and solvent is conducted in this research. Based on this research, it results several types of essential oil in accordance to its solvent and volume variances. By using ethanol as the solvent, it results 250 ml oil (91,433%), 300 ml (91,582%), 350 ml (91,731%), 400 ml (92,030%), and 450 ml (92,179%). Meanwhile, by using n-hexane as the solvent, it results 250 ml oil (91,113%), 300 ml (91,435%), 350 ml (92,081%), 400 ml (92,242%), and 450 ml (92,565%).